2012
DOI: 10.1016/j.gene.2012.09.103
|View full text |Cite
|
Sign up to set email alerts
|

Beyond barcoding: A mitochondrial genomics approach to molecular phylogenetics and diagnostics of blowflies (Diptera: Calliphoridae)

Abstract: Members of the Calliphoridae (blowflies) are significant for medical and veterinary management, due to the ability of some species to consume living flesh as larvae, and for forensic investigations due to the ability of others to develop in corpses. Due to the difficulty of accurately identifying larval blowflies to species there is a need for DNA-based diagnostics for this family, however the widely used DNA-barcoding marker, cox1, has been shown to fail for several groups within this family. Additionally, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

33
168
2
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(206 citation statements)
references
References 102 publications
(127 reference statements)
33
168
2
3
Order By: Relevance
“…All values for maximum intraspecific variations of the Calliphoridae species were no more than 2%. The interspecific variations between species were larger than 5% except for L. cuprina and L. sericata which were no more than 2%, the results was consistent with the previous study (Nelson et al 2012), which indicated that phylogenetic analysis of whole mt genome sequences resulted in much stronger support for discrimination between C. vomitoria and other five species, but week for discrimination between the L. cuprina and L. sericata.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…All values for maximum intraspecific variations of the Calliphoridae species were no more than 2%. The interspecific variations between species were larger than 5% except for L. cuprina and L. sericata which were no more than 2%, the results was consistent with the previous study (Nelson et al 2012), which indicated that phylogenetic analysis of whole mt genome sequences resulted in much stronger support for discrimination between C. vomitoria and other five species, but week for discrimination between the L. cuprina and L. sericata.…”
supporting
confidence: 91%
“…The complete genome was amplified in eight fragments (Nelson et al 2012), and the double-stranded sequence was verified by prime walking within each long polymerase chain reaction (PCR) product. The entire fragments were amplified by TaKaRa MightyAmp Taq (Takara, Dalian, China) and performed on an Eppendorf Mastercycler gradient (Eppendorf, Hamburg, Germany) in 20 lL reaction volume.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The monophyly of the family and its three subfamilies, Miltogramminae, Paramacronychiinae, and Sarcophaginae, has been well supported (Giroux et al, 2010;Kutty et al, 2010;Pape, 1992Pape, , 1996. Little is known about the placement of the Sarcophagidae within the Oestroidea; it has been proposed that the sister family may be either the Tachinidae or the Calliphoridae, or even the still unnamed McAlpine's fly (Kutty et al, 2010;McAlpine, 1989;Nelson et al, 2012;Pape, 1992;Rognes, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The entire genome was amplified in eight fragments (Nelson et al 2012a(Nelson et al , 2012b. All of the fragments were amplified by TaKaRa MightyAmp Taq (Takara, Dalian, China) and performed on an Eppendorf Mastercycler gradient (Eppendorf, Hamburg, Germany).…”
mentioning
confidence: 99%